Population structure and evolutionary history of the greater cane rat (Thryonomys swinderianus) from the Guinean Forests of West Africa - Babarinde, Isaac A.; Adeola, Adeniyi C.; Djagoun, Chabi A. M. S.; Nneji, Lotanna M.; Okeyoyin, Agboola O.; Niba, George; Wanzie, Ndifor K.; Oladipo, Ojo C.; Adebambo, Ayotunde O.; Bello, Semiu F.; Ng’ang’a, Said I.; Olaniyi, Wasiu A.; et al. (Frontiers in Genetics, 2023)
Grasscutter (Thryonomys swinderianus) is a large-body old world rodent found in sub-Saharan Africa. The body size and the unique taste of the meat of this major crop pest have made it a target of intense hunting and a potential consideration as a micro-livestock. However, there is insufficient knowledge on the genetic diversity of its populations across African Guinean forests. Herein, we investigated the genetic diversity, population structures and evolutionary history of seven Nigerian wild grasscutter populations together with individuals from Cameroon, Republic of Benin, and Ghana, using five mitochondrial fragments, including D-loop and cytochrome b (CYTB). D-loop haplotype diversity ranged from 0.571 (±0.149) in Republic of Benin to 0.921 (±0.013) in Ghana. Within Nigeria, the haplotype diversity ranged from 0.659 (±0.059) in Cross River to 0.837 (±0.075) in Ondo subpopulation. The fixation index (FST), haplotype frequency distribution and analysis of molecular variance revealed varying levels of population structures across populations. No significant signature of population contraction was detected in the grasscutter populations. Evolutionary analyses of CYTB suggests that South African population might have diverged from other populations about 6.1 (2.6 – 10.18, 95% CI) MYA. Taken together, this study reveals the population status and evolutionary history of grasscutter populations in the region.